The Epidemiological Situation on Plague in the World and the Forecast of its Development in the Russian Federation for 2025 - N. V. Popov; I. G. Karnaukhov; A. A. Kuznetsov; A. N. Matrosov; A. V. Ivanova; K. S. Martsokha; Sh. V. Magerramov; M. V. Pospelov; V. M. Korzun; D. B. Verzhutsky; E. V. Chipanin; A. V. Kholin; et al. (Проблемы особо опасных инфекций, 2025)
The aim of the review was to assess the epidemiological situation on plague in the world and to forecast its development in the Russian Federation in 2025. Epidemic manifestations of plague in 2015–2024 were registered on the territory of 10 states. The total number of cases was 5880; of which 582 were lethal (the mortality rate reached 9.9 %). In 2024, worldwide, cases of plague were reported in four countries: the Democratic Republic of the Congo (Ituri Province), the Republic of Madagascar (Fianarantsoa Province), the United States of America (Colorado, New Mexico, Oregon), and the People’s Republic of China. A total of 443 cases of plague were registered, of which 17 (3.8 %) had fatal outcome. The Russian Federation reported epidemiological security as regards plague, however, almost every year some of the natural foci show epizootic activity. In 2015–2024, plague-infected animals were detected in 4 natural foci: the Central Caucasian high-mountain, the Gorno-Altai high-mountain, the Tuva mountain, and the Precaspian sandy plague foci. In total, 370 strains of plague agent were isolated in the plague-enzootic territory of the Russian Federation in 2015–2024. The total area of the identified plague epizootics was 15 618.0 km2 . In 2024, local plague epizooties were registered in the Kosh-Agach district of the Altai Republic, Mongun-Taiga Kozhuun of the Republic of Tyva. Plague epizootics were detected on the territory of 2 (Gorno-Altai high-mountain and Tuva mountain) of the 11 natural plague foci of the Russian Federation. The total area of epizootics was 308.9 km2  (2023 – 731.2 km2 ). In total, 8 plague microbe cultures were isolated in 2024 (55 in 2023). Due to the implementation of a set of preventive measures through the efforts of the Rospotrebnadzor institutions, epidemic risks in epizootically active natural foci were significantly reduced, which was the basis for ensuring epidemiological safety as regards plague. The maintaining of the low epizootic potential of the lowland natural plague foci of the Caspian and Trans-Baikal areas in 2025 has been established. The forecast for the sustained tense epidemiological situation in the territory of the Altai Republic and the Republic of Tyva in 2025 is substantiated. The prospects of using the Loginom analytical platform to assess the potential epidemic hazard and predict the epidemiological situation in natural plague foci are outlined.